Microwave heating mechanism and Self-healing performance of scrap tire pyrolysis carbon black modified bitumen. (25th July 2022) - Wang, Fu; Zhu, Hongbin; Li, Yuanyuan; Gu, Dengjun; Gao, Yangming; Feng, Jianlin; Shu, Benan; Li, Chao; Wu, Shaopeng; Liu, Quantao; Xu, Zixuan
Highlights: PCB was used as a wave-absorbing agent for bitumen. PCB was a good electric loss microwave absorbing material. PCB can improve the heating rate and thermal conductance of bitumen. PCB distinctly improved the self-healing rate of bitumen under microwave heating. Abstract: Conventional asphalt mixture has poor microwave absorbing performance and microwave heating efficiency. Based on the characteristics of dielectric loss of scrap tire pyrolysis carbon black (PCB), it is proposed to improve the microwave absorbing performance and self-healing rate of bitumen. The phase composition and electromagnetic parameters of PCB were tested to reveal its microwave heating mechanism. The preparation parameters, heating characteristics and self-healing properties of PCB modified bitumen were studied through the dispersion uniformity test, microwave heating test and SCB test. The main phases of PCB are microwave absorbing carbon and silicon, indicating that PCB is a good electric loss microwave absorbing material. 40 min is the recommended mixing time of 15% PCB modified bitumen. PCB's dosage, microwave frequency and microwave heating time have significant effects on the microwave heating characteristics of PCB modified bitumen. PCB can improve high-temperature stability, thermal conductance, heat storage capacity and self-healing rate of bitumen.